2023
DOI: 10.1177/14574969231175569
|View full text |Cite
|
Sign up to set email alerts
|

Non-obstetric surgery during pregnancy and the effects on maternal and fetal outcomes: A systematic review

Abstract: Background and objective: Non-obstetric surgery is fairly common in pregnant women. We performed a systematic review to update data on non-obstetric surgery in pregnant women. The aim of this review was to evaluate the effects of non-obstetric surgery during pregnancy on pregnancy, fetal and maternal outcomes. Methods: A systematic literature search of MEDLINE and Scopus was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The search span was from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Appendectomy is one of the most common nonobstetric surgeries during pregnancy, and it increases the risk of adverse obstetrical outcomes such as miscarriage and preterm birth [10]. This study found that symptom duration and anorexia were independent risk factors for miscarriage or preterm birth.…”
Section: Discussionmentioning
confidence: 77%
“…Appendectomy is one of the most common nonobstetric surgeries during pregnancy, and it increases the risk of adverse obstetrical outcomes such as miscarriage and preterm birth [10]. This study found that symptom duration and anorexia were independent risk factors for miscarriage or preterm birth.…”
Section: Discussionmentioning
confidence: 77%
“… 7 11 Historically, OA is used more frequently in the third trimester, influenced by concern for iatrogenic injury, loss of domain and risk of preterm birth. 4 14 16 17 Considering LA is more commonly administered in the first trimester, 16 during which fetal loss rates are inherently higher regardless of appendicitis, 18 the causal relationship between fetal demise and the condition is confounded. Recent publications have shown equivalent maternal and fetal outcomes for LA and OA.…”
Section: Case Presentationmentioning
confidence: 99%
“…or because the full text could not be retrieved after searching thoroughly through several libraries and attempting to contact the authors (Appendix B). Eventually, we included 33 articles in our meta-review, 18 SR-only [ 13 - 30 ] and 15 SRs with MA [ 31 - 45 ]. Among them, 23 articles contained non-case report/ non-case series NRSIs or RCTs and were subsequently evaluated with the AMSTAR 2 instrument [ 13 - 16 , 18 - 20 , 30 - 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…Eventually, we included 33 articles in our meta-review, 18 SR-only [ 13 - 30 ] and 15 SRs with MA [ 31 - 45 ]. Among them, 23 articles contained non-case report/ non-case series NRSIs or RCTs and were subsequently evaluated with the AMSTAR 2 instrument [ 13 - 16 , 18 - 20 , 30 - 45 ]. Figure 1 illustrates the flowchart of study selection.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation